Teacher prototypes in technology-enhanced instruction in elementary school second language acquisition: Comparing routine and emergency learning in different cultures - Esti Schwartz; Tamar Shamir-Inbal; Ina Blau (Computers and Education Open, 2023)
Over the past decade, learning cultures worldwide have been affected differently by the rapid spread of educational technology. During emergency distance learning, teachers had to adapt themselves to a new mode of learning. The purpose of this study was to compare technology-integrated instructional strategies and teacher prototypes in three learning cultures during routine and emergency learning based on the Five Spaces for Design in Education framework (Weiner et al., 2020). The participants were 31 teachers from three regions - Eastern Europe, Western Europe, and Northern America, all integrating the same adaptive digital learning environment in second language instruction. Participants' interviews were coded according to a three level tier of instructional strategies (n = 938) denoting the student's place in the learning process and level of independence, as well as a categorization of four teacher prototypes representing the degree of teacher centrality in the classroom (n = 764): sage, facilitator, guide, and partner. Chi-square tests highlighted the differences in instructional strategies and teacher centrality between the learning cultures in the three regions. The findings of the teacher prototype analysis showed a similar distribution of prototypes among the three regions, both in routine learning and emergency times. Regarding instructional strategies, each culture showed a unique tendency to specific strategies, while in the transition to emergency learning there was a convergence to strategies with the medium level of teacher control over students and a certain degree of student independence.